THE SIGNIFICANCE OF THE INFLUENCE OF INTANGIBLE FACTORS OF MOTIVATION OF ENTERPRISE PERSONNEL - Romaniuk, M.D.; Romaniuk, T.M. (The actual problems of regional economy development, 2023)
The integration of the Ukrainian economy into the EU and other international structures requires fundamental changes in the motivation of labor and intellectual potential of enterprise personnel. The main purpose of the motivation process is getting the maximum return on the use of the available labor and resource potential, which allows to increase the overall efficiency and profitability of enterprises with the effective use of tangible and intangible factors. The article considers the influence of intangible factors on the motivation of enterprise personnel. It is determined that the effectiveness of the motivation system under the current conditions implies not only tangible factors, such as high earnings, but also intangible factors associated with the reliability of the place of work, with the achievement of one's own goals, and the desire to take initiative and responsibility. It is connected with the fact that often motivational mechanisms take into account only the material component, leaving aside the intangible component, and therefore the author proposes to form a motivational mechanism which should take into account both tangible motivation and identification and implementation of intangible factors of labor motivation of enterprise personnel. It is found and characterized that the main intangible factors that encourage staff to work more efficiently include: proper working conditions; socio-psychological climate; personal example of the manager; individual approach to the employee; deadlines for completing tasks; consideration of the interests and capabilities of the employee; support for employees in continuous training, advanced training, as well as opportunities for self-development and self-expression of employees. It is substantiated that the non-traditional methods of staff motivation include moral incentives, paternalism, organizational incentives, participation in management, career and development, participation in profits and capital. It is proposed to widely use non-traditional types of non-material motivation, in particular: instrumental, professional, patriotic, and economic.